Antibacterial activity and virtual screening by molecular docking of lycorine from Pancratium foetidum Pom (Moroccan endemic Amaryllidaceae). (February 2018) - Bendaif, H.; Melhaoui, A.; Ramdani, M.; Elmsellem, H.; Douez, C.; El Ouadi, Y.
Abstract: Lycorine is an alkaloid isolated from bulbs of Pancratium foetidum Pom Amaryllidaceae of the genus Lycoris. It has very strong pharmacodynamics properties and biological effects, among others, antimalarial, antiviral, antitumor, and anti-inflammatory. Lycorine has been identified and characterized by thin layer chromatography, IR and NMR (1H and 13C NMR, COZY, HMBC, HSQC and NOESY). The antibacterial activity of lycorine has been evaluated. Lycorine has a moderate antibacterial activity on the majority of strains studied, nevertheless it is more effective than Streptomycin and Ampicillin against bacteria: P. aeruginosa, En. cloacae. To confirm these results, it is necessary to use qualitative techniques and methods, etc… We performed a virtual docking ligand-lycorine protein screening study to predict and characterize their mode of interaction with the LpxC receptor. Docking results have shown that lycorine can interact with target amino residues studied by hydrogen and metal-ion bonds. In addition, the ADME-Tox profile study has shown that lycorine is all in agreement, either with Lipinski's critics or with the toxicity standards. Highlights: Identification and characterization of lycorine by CCM, IR, NMR (1H and 13C, COZY, HMBC and NOESY). Moderate antibacterial activity of lycorine in all strains studied. Lycorine can interact with target amino residues studied by hydrogen and metal ion bonds. ADME-TOX profile showed that lycorine strongly agrees with Lipinski's critics or toxicity standards.